Are very high rates of exogenous carbohydrate ingestion (>90 g/hr) sufficient or indeed necessary to run a sub-2hr marathon? An analysis of the model predictions of Lukasiewicz and colleagues - Noakes, T. D.; Prins, P. J. (Frontiers in Nutrition, 2025)
Lukasiewicz et al. (1) have published a model which predicts that to run a sub-2hr marathon (sub2hrM), prospective male and female runners will need to oxidize ingested (exogenous) carbohydrate (CHO) at respective rates of 93 and 108 g/hr during that race. Their predictions are dependent on the assumptions of their model.